The Influence of Ownership Structure on Stock Repurchase Policy of Companies Listed in Indonesia Stock Exchange - Awangga Perdana; Siti Nurwahyuningsih Harahap (The Indonesian Journal of Accounting Research, 2015)
Abstract: This study examines the influence of ownership structure on firms in Indonesia for their stock repurchase policy aimed to distribute excess funds to stockholders. Ownership structure studied consists of institutional ownership and managerial ownership. A sample of this study consists of 41 companies listed in the Indonesia Stock Exchange that repurchased their stocks from 2004 to 2013. The results showed that institutional investors and managerial ownership negatively affect the stock repurchase. Institutional ownership is considered able to be a useful monitoring tool to monitor the use of free cash flow in the company and mechanisms of control by the manager himself against the use of free cash flow is considered good. Moreover, they prefer to invest surplus funds in developing the company's business enterprises.Abstrak: Penelitian ini menguji pengaruh struktur kepemilikan pada perusahaan di Indonesia atas kebijakan pembelian kembali saham mereka yang bertujuan untuk mendistribusikan kelebihan dana kepada pemegang saham. Struktur kepemilikan yang dipelajari terdiri dari kepemilikan institusional dan kepemilikan manajerial. Sampel dari penelitian ini terdiri dari 41 perusahaan yang terdaftar di Bursa Efek Indonesia yang membeli kembali saham mereka selama periode 2004-2013. Hasil penelitian menunjukkan bahwa investor institusional dan kepemilikan manajerial berpengaruh negatif terhadap pembelian kembali saham. Kepemilikan institusional dianggap mampu menjadi alat pemantauan yang baik untuk memantau penggunaan arus kas bebas di perusahaan dan mekanisme kontrol oleh manajer sendiri terhadap penggunaan arus kas bebas dianggap baik. Selain itu, mereka lebih suka menginvestasikan dana surplus untuk mengembangkan perusahaan bisnis perusahaan.